أثر الأمراض الوراثية على أحكام الزواج "دراسة فقهية مقارنة" - سعيدي, رتيبة (University of Eloued-جامعة الوادي, 2015)
Find addressed the subject of a study on the impact of genetic diseases where he addressed the provisions of the marriage in the first part, the concept of genetic diseases with a statement such as the position of Islamic law. The second topic was touched to a statement on the impact of genetic diseases provisions of the engagement and the concept of the medical examination before marriage, the most important benefits and objectives of the rule also addressed the distinction between spouses because of genetic disease. In the final statement was the impact of genetic diseases to offspring through the study of the rule of contraception because of genetic disease, as well as the position of the law of abortion deformed fetus because of the genetic disease, and in the last of this study concluded a set of findings and recommendations reached them.
مذكرة ماستر
Keywords: الأمراض الوراثية/أحكام الزواج; Hereditary diseases/marriage provisions